2016
DOI: 10.2105/ajph.2016.303423
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Jails and Prisons: United States, 2002−2013

Abstract: Objectives To describe cases and estimate the annual incidence of tuberculosis in correctional facilities. Methods We analyzed 2002 to 2013 National Tuberculosis Surveillance System case reports to characterize individuals who were employed or incarcerated in correctional facilities at time they were diagnosed with tuberculosis. Incidence was estimated with Bureau of Justice Statistics denominators. Results Among 299 correctional employees with tuberculosis, 171 (57%) were US-born and 82 (27%) were female.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 21 publications
1
27
0
3
Order By: Relevance
“…A study conducted in the USA by Lambert et al [ 11 ] found 299 cases of active TB among prison employees in 35 US states; 49% of the diagnoses were made at the onset of clinical symptoms, 31% of the diagnoses were incidental, 11% were made through occupational health surveillance, and 9% were made through contact investigations of contagious cases.…”
Section: Summary Of Studies Includedmentioning
confidence: 99%
“…A study conducted in the USA by Lambert et al [ 11 ] found 299 cases of active TB among prison employees in 35 US states; 49% of the diagnoses were made at the onset of clinical symptoms, 31% of the diagnoses were incidental, 11% were made through occupational health surveillance, and 9% were made through contact investigations of contagious cases.…”
Section: Summary Of Studies Includedmentioning
confidence: 99%
“…Globally, rates of TB cases in correctional facilities are 26 times higher compared with the general population [ 4 ]. Although TB incidence rates among correctional populations in the United States have been shown to be steadily declining recently, incarcerated populations continue to experience TB at a substantially higher incidence than in the general population [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Incidence rates among correctional populations have been shown to be consistently higher than overall TB rates in the United States, and up to eight times higher than among non-correctional populations. 3,4 Several outbreaks in correctional facilities have been reported, some resulting in transmission to the community. 5–10 …”
mentioning
confidence: 99%